Interest in Health Information Exchange in Ambulatory Care: A Statewide Survey - Tham, E.; Ross, S. E.; Mellis, B. K.; Beaty, B. L.; Schilling, L. M.; Davidson, A. J. (Applied Clinical Informatics, 2010)
Objective: Assess the interest in and preferences of ambulatory practitioners in HIE.Background: Health information exchange (HIE) may improve the quality and efficiency of care. Identifying the value proposition for smaller ambulatory practices may help those practices engage in HIE.Methods: Survey of primary care and specialist practitioners in the State of Colorado.Results: Clinical data were commonly (always [2%], often [29%] or sometimes [49%]) missing during clinic visits. Of 12 data types proposed as available through HIE, ten were considered “extremely useful” by most practitioners. “Clinical notes/consultation reports,” “diagnosis or problem lists,” and “hospital discharge summaries” were considered the three most useful data types. Interest in EKG reports, diagnosis/problem lists, childhood immunizations, and discharge summaries differed among ambulatory practitioner groups (primary care, obstetrics-gynecology, and internal medicine subspecialties).Conclusion: Practitioners express strong interest in most of the data types, but opinions differed by specialties on what types were most important. All providers felt that a system that provided all data types would be useful. These results support the potential benefit of HIE in ambulatory practices.
Keywords: Ambulatory care information systems; communication; questionnaires